ENHANCING RED ONION (Allium cepa L.) GROWTH AND YIELD THROUGH CONTROLLED TUBER CUTTING AND PLANT GROWTH REGULATOR APPLICATION - Hastin Ernawati Nur Chusnul Chotimah; Caini Hawini; Siti Zubaidah; Wahyu Widyawati; Sustiyah (BPFP Universitas Bengkulu, 2024)
The synergistic effects of tuber cutting and PGR application on red onion growth and yield have not been extensively studied. Therefore, this study aimed to determine the most effective combination of tuber cutting and plant growth regulator (PGR) application for enhancing red onion growth and yield. Conducted between January and April 2023 in the greenhouse of the Agronomy Department, Faculty of Agriculture, University of Palangka Raya, the experiment utilized a completely randomized design (CRD) with seven treatments, each repeated five times. Treatments included: no cutting, cutting ¼ part of the bulb + 3 mL/L PGR, cutting ¼ part of the bulb + 6 mL/L PGR, cutting ¼ part of the bulb + 9 mL/L PGR, cutting ⅓ part of the bulb + 3 mL/L PGR, cutting ⅓ part of the bulb + 6 mL/L PGR, and cutting ⅓ part of the bulb + 9 mL/L PGR. Results indicate that red onion growth and yield can be significantly optimized through the strategic combination of tuber cutting and PGR application. The treatment involving cutting one-third of the tuber with 6 mL/L PGR concentration yielded the most favorable outcomes. Plants in this treatment displayed an average height of 45.84 cm, 51.4 leaves per plant, 10.6 bulbs per plant, 12.4 tillers per plant, a fresh weight of 42.79 g, a tuber dry weight of 18.34 g, and a bulb diameter of 2.18 cm. These findings suggest that cutting one-third of the bulb, in conjunction with specific PGR concentrations, enhances both yield and nutrient content in red onion bulbs, offering valuable insights for optimizing cultivation practices and maximizing crop productivity.